(untitled) (Comparatismi, 2017)
ABSTRACT L’ipotesi di ricerca si interroga sulle possibili caratteristiche di un prototipo di storia che agevoli le performance comunicative deficitarie. A partire dalle teorie sulla struttura metaforica delle narrazioni e lo sviluppo della competenza empatica, l’articolo esplora il potenziale terapeutico delle storie fondato sulla capacità di simulare relazioni parasociali e preparare la sfera cognitiva ed emotiva a confrontarsi con l’alterità. Viene tracciato uno schema narrativo al fine di facilitare la comprensione dei significati e tradurli in contenuti di comunicazione. L’analisi comprende aspetti dello story-grammar e della narrazione audiovisiva, per mezzo di studi sulle competenze di storytelling nelle persone con sindrome autistica e test sull’attaccamento emotivo alle storie fruite in video. ABSTRACT The research hypothesis examines the possible features of a narrative prototype to facilitate difficult communication performances. Starting from theories about the metaphorical structure of narratives and the development of empathic competence, the article explores the therapeutic potential of stories based on the ability to simulate social relationships and prepare the cognitive and emotional sphere to deal with otherness. A narrative scheme is defined in order to support the understanding of meanings and to translate them into communication contents. The analysis includes aspects of story-grammar and audiovisual narrative, through studies about storytelling skills in people with Autism Spectrum Conditions and tests on emotional attachment to stories on video.